“Matando o Desconhecimento”: The Role of Culture in Brazil’s Relations with Canada and Beyond - Hewitt, W. E. (Ted); Gomes, Inês C. (Canada and Beyond: A Journal of Canadian Literary and Cultural Studies, 2017)
In recent years, observers in both Canada and Brazil have pointed to the benefits of further developing relations between the two countries. Despite diplomatic efforts to promote productive interchange however, levels of trade – perhaps the most salient barometer of relationship health – have remained both modest and relatively stagnant. This is true, moreover, in spite of broad advances made by Brazil in particular in relationship building elsewhere. This paper seeks to explore the roots of this seeming paradox by examining the factors that appear to have facilitated the growth of diplomatic and trade relations between Brazil and partners other than Canada – specifically in Africa; relations rooted primarily in a strategy of “cultural approximation”. The potential role of cultural factors in promoting the Canada-Brazil relationship is then explored in this light, focusing on recent efforts to support enhanced educational and scientific interchange between the two countries.